Optimization of holding time on microwave irradiation of the composite iron-chromium reinforced with alumina particle - Wan Abdul Rahman Assyahid, Wan Ibrahim (Trans Tech Publications Ltd., 2019)
Link to publisher's homepage at https://www.scientific.net